HIV Screening During Pregnancy in a U.S. HIV Epicenter - Alec Szlachta-McGinn; Alexandra Aserlind; Lunthita Duthely; Sean Oldak; Ruchi Babriwala; Emily Montgomerie; JoNell Potter (Hindawi Limited, 2020)
Background. The CDC and ACOG have issued guidelines for HIV screening in pregnancy for patients living in areas with high prevalence of HIV in order to minimize perinatal vertical transmission. There is a lack of data examining providers' compliance with these guidelines in at-risk patient populations in the United States. Objective. To evaluate if HIV screening in pregnant women was performed according to guidelines at a large, urban, tertiary care medical center in South Florida. Study Design. A retrospective review was performed on 1270 prenatal and intrapartum records from women who delivered a live infant in 2015 at a single institution. Demographic and outcome data were chart abstracted and analyzed using arithmetic means and standard deviations. Results. Of the 1270 patients who met inclusion criteria, 1090 patients initiated prenatal care in the first or second trimester and delivered in the third trimester. 1000 (91.7%) patients were screened in the first or second trimester; however, only 822 (82.2%) of these were retested in the third trimester during prenatal care. Among the 178 patients lacking a third trimester test, 159 (89.3%) received rapid HIV testing upon admission for delivery. Of the 1090 patients who initiated prenatal care in the first or second trimester and delivered in the third trimester, 982 (90.1%) were screened in accordance with recommended guidelines. Of the 1270 patients initiating care in any trimester, 24 (1.9%) had no documented prenatal HIV test during prenatal care, however 22 (91.7%) had a rapid HIV test on admission for delivery. Two (0.16%) patients were not tested prenatally or prior to delivery. Conclusion. Despite 99.8% of women having at least one HIV screening test during pregnancy, there is room for improvement in routine prenatal screening in both early pregnancy and third trimester prior to onset of labor in this high-risk population.